A Hospital-Based Study: Interventions for Patients with Disorders of Sex Development (DSD) in National Reference Hospital, South Sumatera Region, Indonesia - Ziske Maritska; Bintang Arroyantri Prananjaya; Andhika Diaz Maulana (HM Publisher, 2019)
ABSTRACT Background. Disorders of Sex Development (DSD) is a term used to describe a congenital condition where sex chromosomes, gonads, and or anatomy of a person are atypical. It is estimated to affect 1:4,500 people worlwide with varied clinical findings, hence the integrated and diverse interventions. Objective. This study wished to observe the many interventions DSD patients received in Dr. Mohammad Hoesin Hospital as one of the national reference hospitals in Indonesia for South Sumatera region. Methods. Medical records of 173 patients with clinical findings in accordance with DSD spectrum during 2013-2017 was observed in order to identify both surgical and medical interventions applied. Results. Sixty two patients were diagnosed of having hypospadias (35.84%), making it the most common clinical finding among DSD patients in this hospital. Surgical intervention was the most favored intervention, with 155 patients (89.6%) underwent various surgeries, ranging from urethroplasty to vaginoplasty and many more. Five patients(2.9%) were treated with either hydrocortisone and florinef, or both. One patient diagnosed with Congenital Adrenal Hyperplasia (CAH) had both surgical and medical intervention. Conclusion. DSD gives a wide phenotypic spectrum, making its management both challenging and complicated. Surgical, medical, and or a combination of both are the indispensable interventions when dealing with DSD patients. Study focusing on psychological intervention for DSD patients is further needed. Keyword: Disorders of Sex Development, DSD, surgical, medical, intervention.